HERMENEUTIKA HUKUM ISLAM DALAM MENINJAU PERUBAHAN USIA MINIMUM PERNIKAHAN - M. Khoirul Muzakki (Prodi Hukum Keluarga Islam IAI Uluwiyah Mojokerto, 2025)
Setting a minimum age for marriage is a big debate because it involves protecting children, ensuring fairness between men and women, and understanding Islamic laws. The study uses a method called hermeneutics to better understand how Islamic law can be interpreted when it comes to changing the minimum age for marriage. It also looks at how people's opinions on this issue have changed over time, especially as more attention is given to women's rights. Because of these changes, the research tries to find arguments that either support or against raising the minimum age for marriage from an Islamic law point of view. The goal is to get a better understanding of how Islamic law is interpreted in this area and how it can help protect women's rights and lead to positive changes in Muslim communities. By learning how hermeneutics helps interpret Islamic law, there is hope that better policies can be created that follow both Islamic principles and human values.